Preparation method and application of magnetic response multifunctional super-hydrophobic biomass aerogel
By combining chitosan with CMIL-101 and hydrophobizing treatment, a magnetically responded multi-function superhydrophobic aerogel was prepared, which solved the problem of reduced adsorption capacity caused by the hydrophilicity of existing materials, and achieved efficient oil-water separation and micro-micro Plastic removal, with excellent magnetic and photothermal conversion performance, suitable for multifunctional water pollution control.
Patent Information
- Application Number
- CN202411489737.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing superhydrophobic materials have hydrophilic problems in oil-water separation and microplastic adsorption, resulting in reduced adsorption capacity and it is difficult for multifunctional materials to achieve efficient oil-water separation and microplastic removal.
Magnetic response multi-functional superhydrophobic biomass aerogel is prepared by freeze-drying technology. By combining chitosan with CMIL-101 and hydrophobicized using hydrophobic materials, it forms a high specific surface area, low density and open pore structure. Aerogels achieve efficient adsorption of oils and microplastics.
It realizes efficient adsorption of oil-water separation and microplastics, has excellent magnetic and photothermal conversion performance, can maintain adsorption effect in harsh environments, and reduces production costs.
Smart Images

Figure CN119186420A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of super-hydrophobic materials, and in particular relates to a preparation method and application of a magnetically responsive multifunctional super-hydrophobic biomass aerogel. Background Art
[0002] Oily wastewater is a type of wastewater generated during the production of oil, oil refining, and petrochemicals. In addition, oil spills from ships inevitably lead to the presence of grease in freshwater resources. Wastewater not only causes damage to the ecological environment, but also affects people's health because toxic components can evaporate into the air and be absorbed by the human body through the skin and breathing. At the same time, the SARS-CoV-2 virus exists in untreated sewage, and the flow of harmful water provides a pathway for the spread of the virus. If oily wastewater is discharged directly, it will increase the turbidity of natural water and have a bad impact on the production and living environment. In addition, microplastics (MPs) are also ubiquitous in aquatic and terrestrial environments, and MPs can cause ecological hazards, bioaccumulation, water pollution, and disruption of water cycles in the environment. Although various filtration and adsorption materials have been developed to purify sewage, many existing solutions are limited by their single function and are only targeted at specific types of wastewater. There is an urgent need to innovate economical and environmentally friendly multifunctional materials to achieve oil-water separation and remove emerging pollutants.
[0003] In recent years, superhydrophobic materials have been widely welcomed due to their excellent oil absorption selectivity and waterproof properties, and are ideal materials for separation of oil-water mixtures and emulsions. Porous materials with excellent oil-water separation efficiency, such as aerogels, porous membranes and sponges, have attracted widespread attention, especially chitosan aerogels. Chitosan molecules contain a large number of active groups such as amino groups and hydroxyl groups, which can provide many active sites for chemical reactions. In addition, chitosan is widely available in nature, cheap, biocompatible, and biodegradable, making it a good skeleton material. Therefore, it gives chitosan aerogels the advantages of high specific surface area, low density, high porosity, open cell structure, good mechanical properties, and low cost, making them suitable for oil-water separation and MPs adsorption. However, pure chitosan aerogels exhibit hydrophilicity, which means that they will adsorb water and MPs at the same time, which greatly reduces their adsorption capacity for MPs and even destroys their mechanical behavior. Therefore, we need to modify pure chitosan aerogels so that they can selectively absorb oil or water to achieve oil-water separation, and are expected to obtain better absorption performance and higher recyclability when removing MPs, thereby realizing the multifunctional application of MPs adsorption and oil-water separation. Summary of the invention
[0004] The present invention adopts freeze-drying technology to prepare multifunctional aerogel, uses chitosan as a carrier to support CMIL-101 to give it magnetism, and uses hydrophobic materials for hydrophobic treatment. The obtained aerogel has a high adsorption capacity for MPs and oil, and the removal efficiency is close to 100%.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a magnetically responsive multifunctional super-hydrophobic biomass aerogel comprises the following steps:
[0007] 1) dissolving ferric chloride hexahydrate in N,N-dimethylformamide to form solution A, dissolving terephthalic acid in solution A to form solution B, hydrothermal reaction, centrifugal washing, drying, and calcining to obtain CMIL-101;
[0008] 2) adding CMIL-101 to deionized water, adding chitosan CS and acetic acid, stirring vigorously to form a high-viscosity chitosan hydrogel, and freeze-drying to obtain CMIL-101 / CS aerogel;
[0009] 3) The hydrophobic material and the curing agent are dissolved in an organic solvent and stirred to obtain a uniform suspension, the CMIL-101 / CS aerogel is immersed in the suspension, and then the mixed system is vacuum dried to obtain a magnetically responsive multifunctional super-hydrophobic chitosan aerogel PDMS@CMIL-101 / CS.
[0010] Furthermore, in the above preparation method, in step 1), the molar ratio of ferric chloride hexahydrate: terephthalic acid is 2:1.
[0011] Furthermore, in the above preparation method, in step 1), the hydrothermal reaction is carried out at 110° C. for 20 hours.
[0012] Furthermore, in the above preparation method, in step 1), the calcination condition is calcination at 500° C. for 2 h.
[0013] Furthermore, in the above preparation method, in step 2), the mass ratio of chitosan CS:CMIL-101 is 5 to 10:1.
[0014] Preferably, in the above preparation method, in step 2), the mass ratio of chitosan CS:CMIL-101 is 10:1.
[0015] Furthermore, in the above preparation method, in step 3), the hydrophobic material is selected from stearic acid, lauric acid, PFTEOS or polydimethylsiloxane.
[0016] Preferably, in the above preparation method, in step 3), the hydrophobic material is polydimethylsiloxane.
[0017] Furthermore, in the above preparation method, in step 3), the curing agent is diphenylbutyl carbamate.
[0018] Furthermore, in the above preparation method, in step 3), the organic solvent is n-hexane.
[0019] The magnetically responsive multifunctional superhydrophobic biomass aerogel PDMS@CMIL-101 / CS prepared by any of the preparation methods described above is used as an adsorbent in removing organic pollutants.
[0020] Furthermore, the above application method is as follows: take an aqueous solution containing organic pollutants, adjust the solution to neutrality, then add magnetically responsive multifunctional superhydrophobic biomass aerogel PDMS@CMIL-101 / CS, oscillate and adsorb, and then separate using a magnet.
[0021] Preferably, in the above application method, the pH of the aqueous solution containing organic pollutants is adjusted to 7.
[0022] Furthermore, in the above application, the organic pollutants are microplastic organic matter.
[0023] Preferably, in the above application, the microplastic organic matter is polystyrene microplastic.
[0024] The magnetically responsive multifunctional superhydrophobic biomass aerogel PDMS@CMIL-101 / CS prepared by any of the preparation methods described above is used as an adsorbent in oil-water separation.
[0025] Furthermore, the above application method is as follows: adding magnetically responsive superhydrophobic chitosan aerogel PDMS@CMIL-101 / CS into the oil-water mixture and allowing it to stand for adsorption.
[0026] Furthermore, in the above application, the oil includes n-hexane, n-pentane, dichloromethane, ethyl acetate, N,N-dimethylformamide, chloroform, motor oil, peanut oil or olive oil.
[0027] The beneficial effects of the present invention are:
[0028] 1. Compared with pure chitosan aerogel, the PDMS@CMIL-101 / CS of the present invention has a higher specific surface area, lower density, higher porosity, more open pore structure and better mechanical properties, providing a new strategy for water pollution control.
[0029] 2. The PDMS@CMIL-101 / CS of the present invention can simultaneously adsorb MPs and separate oil and water, and also has a good removal effect on other new pollutants, and still has excellent adsorption effect in harsh environments such as strong acids and strong salts.
[0030] 3. The PDMS@CMIL-101 / CS of the present invention has excellent magnetic and photothermal conversion properties, enabling autonomous adsorption of oil under a magnetic field, and facilitating the treatment of high-viscosity oils, simplifying the separation process. This work contributes to the development of multifunctional bio-based adsorbents for effective water remediation.
[0031] 4. The preparation method of the present invention does not require expensive reagents and equipment, nor does it require harsh experimental conditions, which greatly reduces the production cost. The synthesized aerogel has magnetic response characteristics and can achieve efficient and controllable oil-water separation. These materials, with their high specific surface area, low density, high porosity, open pore structure and excellent mechanical properties, provide a new strategy for water pollution control, which is of great significance to promoting the development of oil-water separation technology and ecological environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the synthesis of PDMS@CMIL-101 / CS aerogel.
[0033] Figure 2 Photos of PDMS@CMIL-101 / CS aerogel on pine branches (a) and flower cores (b).
[0034] Figure 3 It is the FT-IR spectrum of PDMS@CMIL-101 / CS aerogel.
[0035] Figure 4 It is the effect of adding hydrophobic materials on the removal of microplastics.
[0036] Figure 5 These are the stability test diagrams of PDMS@CMIL-101 / CS aerogel, (a) is the mechanical stability measured by sandpaper friction, (b) is the light oil separation cycle stability, and (c) is the heavy oil separation cycle stability.
[0037] Figure 6 (a) Photo of water droplets on PDMS@CMIL-101 / CS, (b) Photo of PDMS@CMIL-101 / CS showing perfect water repellency under water flux, and (c) Photo of the silver mirror phenomenon of PDMS@CMIL-101 / CS immersed in water.
[0038] Figure 7 It is the absorption capacity diagram of PDMS@CMIL-101 / CS in different organic solvents.
[0039] Figure 8 These are photos of the absorption process of dichloromethane (a) and n-hexane (b) by PDMS@CMIL-101 / CS.
[0040] Fig. 9 These are photos of dynamic oil-water separation (pump separation) of oils with different densities using PDMS@CMIL-101 / CS.
[0041] Fig.10 is an optical image of the clockwise magnetically driven spiral oil absorption motion of PDMS@CMIL-101 / CS.
[0042] Fig.11 Photos of the wetting behavior of high viscosity oil on top of the PDMS@CMIL-101 / CS surface under no illumination (a) and illumination (b).
[0043] Fig.12 These are photos of the hydrophobicity of PDMS@CMIL-101 / CS under different harsh environments. DETAILED DESCRIPTION
[0044] Example 1 Magnetic responsive multifunctional superhydrophobic biomass aerogel (PDMS@CMIL-101 / CS)
[0045] (I) The preparation method is as follows:
[0046] The synthetic route of PDMS@CMIL-101 / CS is as follows: Figure 1 .
[0047] 1) Preparation of CMIL-101:
[0048] 4.9 mmol of ferric chloride hexahydrate was dissolved in 30 mL of N,N-dimethylformamide to form solution A, and 2.48 mmol of terephthalic acid was dissolved in solution A to form solution B. The solution was subjected to hydrothermal reaction at 110° C. for 20 h. The precipitate was collected by centrifugation, washed, and dried. The product was calcined at 500° C. for 2 h to obtain CMIL-101.
[0049] 2) Preparation of CMIL-101 / CS aerogel:
[0050] 0.2 g CMIL-101 was added to 20 mL deionized water, and then 2.0 g chitosan (CS) was added to the mixed solution. 0.8 mL acetic acid solution was slowly added and stirred vigorously to form a high-viscosity chitosan hydrogel. The mixture was freeze-dried for 24 h to obtain CMIL-101 / CS aerogel.
[0051] 3) Preparation of PDMS@CMIL-101 / CS:
[0052] 0.847 g PDMS (polydimethylsiloxane) and 0.0847 g curing agent (butyl diphenylcarbamate) were dissolved in 50 mL n-hexane and stirred for 5 min to obtain a uniform suspension. CMIL-101 / CS aerogel was immersed in the suspension and vacuum dried to obtain magnetically responsive superhydrophobic chitosan aerogel PDMS@CMIL-101 / CS.
[0053] (II) Testing
[0054] PDMS@CMIL-101 / CS aerogel is ultra-light, such as Figure 2 As shown, the aerogels can be placed on relatively light substrates (such as flower cores and pine branches) without losing their shape. In addition, the simple and controllable method ensures that aerogels can be easily designed and manufactured into ideal shapes (such as cubes, 3D polygons and other complex 3D shapes) for various applications.
[0055] like Figure 3 As shown in the FTIR spectrum, at 1450 cm -1 The peak observed at 802 cm is due to the symmetrical (OCO) vibration absorption peak in CMIL-101, which confirms the presence of BDC (phthalic acid) linker in CMIL-101(Cr). -1 、1091cm -1 and 1260cm -1 The broad peaks are Si-C stretching vibration, Si-O-Si and Si-CH3 stretching vibration, indicating that PDMS is successfully deposited on the sample.
[0056] Example 2 Application of magnetically responsive multifunctional superhydrophobic biomass aerogel PDMS@CMIL-101 / CS in removing microplastic organic matter
[0057] Method: Add aerogel to 10mL10mg·L -1 Oscillating adsorption was carried out in a microplastic (MPs) solution (pH of the solution was 7), and the residual MPs in the suspension were detected by a fluorescence spectrophotometer.
[0058] The adsorption rate (η) was calculated by the following formula:
[0059]
[0060] Where, C0 (mg / L) is the initial concentration of MPs; C t (mg / L) is the concentration of MPs in the solution after adsorption.
[0061] 1. Effect of adding hydrophobic materials on microplastic removal
[0062] In order to explore whether the addition of materials enhances the performance of aerogels, the adsorption performance of aerogels at various stages on microplastics was studied.
[0063] Pure CS and the two aerogels CMIL-101 / CS and PDMS@CMIL-101 / CS prepared in Example 1 were added with 10 mL of 10 mg·L -1 The microplastic solution (pH 7) was adsorbed under oscillation at 25°C for 1 h. After the adsorption was completed, a magnet was used to separate the material from the sample solution under the action of an external magnetic field, and a fluorescence spectrophotometer was used to detect the residual MPs in the sample solution. Figure 4 .
[0064] from Figure 4 It can be seen that the removal rate of MPs increased significantly with the addition of CMIL-101, which is due to the electrostatic attraction and π-π interaction between MPs and CMIL-101. When PDMS was added, the removal rate increased slightly and the mechanical properties increased. Therefore, PDMS and CMIL-101 significantly increased the adsorption performance of aerogels for microplastics.
[0065] (II) Stability test
[0066] Explore the mechanical durability and chemical stability of superhydrophobic materials, especially their reusability and operational adaptability.
[0067] Implementation method: The cyclic compression and mechanical friction of light oil and heavy oil are used to simulate the extreme conditions. The PDMS@CMIL-101 / CS aerogel is placed in the above environment to evaluate the physical and chemical stability of the material.
[0068] The results are as follows Figure 5 As shown, Figure 5 (a) is the mechanical stability measured by sandpaper friction. It can be seen that the superhydrophobic contact angle is still relatively high after multiple cycles. Figure 5 (b) is the light oil separation cycle stability. Figure 5 (c) shows the cycle stability of heavy oil separation. It can be seen that the separation efficiency remains high after multiple cycles. Therefore, it can be concluded that the mechanical durability and chemical stability of this PDMS@CMIL-101 / CS aerogel are very good.
[0069] Example 3 Application of magnetically responsive multifunctional superhydrophobic biomass aerogel PDMS@CMIL-101 / CS in oil-water separation
[0070] The application of aerogel as adsorbent material in oil-water separation was investigated.
[0071] Adsorption capacity is a standard for evaluating the performance of oil-absorbing materials and can be measured by the following procedure. A single aerogel is weighed and then placed in different types of oils and organic solvents for adsorption tests. After adsorption saturation, it is taken out and the oil and organic solvent on the surface are wiped off with filter paper, and then the aerogel after oil absorption is weighed. The adsorption capacity (Q) is calculated by the following formula:
[0072]
[0073] Among them, m0 and m1 are the weights of aerogel before and after adsorption, respectively.
[0074] (I) Wetting ability of PDMS@CMIL-101 / CS
[0075] like Figure 6 As shown, the water droplets maintain a stable spherical shape on the PDMS@CMIL-101 / CS surface ( Figure 6 PDMS@CMIL-101 / CS also exhibits strong repellency to the impinging water flow ( Figure 6 b). A large number of bubbles appear around the surface of PDMS@CMIL-101 / CS in water, resulting in mirror reflection ( Figure 6 (c).
[0076] (II) Saturated adsorption of PDMS@CMIL-101 / CS on different oils and organic solvents
[0077] The saturated adsorption capacity of PDMS@CMIL-101 / CS for three oils (motor oil, peanut oil, and olive oil) or organic solvents (ethanol, n-hexane, n-pentane, N, N-dimethylformamide, dichloromethane, chloroform, and ethyl acetate) was investigated.
[0078] The magnetically responsive superhydrophobic chitosan aerogel PDMS@CMIL-101 / CS was added to the oil-water mixture and allowed to stand for adsorption.
[0079] Depend on Figure 7 It can be seen that the absorption capacity depends on the density and viscosity of the oils and organic solvents. The absorption capacity is the lowest when the organic solvent is n-hexane. The absorption capacity is the highest when the oil is peanut oil, reaching 10 times its own weight. The recyclability of these oils and organic solvents was evaluated, and there was no significant decrease in the absorption capacity after 12 cycles of adsorption and desorption. This excellent recyclability is mainly due to the chemical durability, porous structure and strong layered roughness of the PDMS layer.
[0080] (III) Practical application
[0081] The practical application of PDMS@CMIL-101 / CS in oil spill cleanup was investigated, simulating the separation of mixed oil from a mixture under natural conditions. The selective adsorption experiments were conducted using Sudan III-dyed n-hexane (light oil) and dichloromethane (heavy oil) mixed with water.
[0082] Depend on Figure 8 It can be seen that PDMS@CMIL-101 / CS can selectively adsorb n-hexane and dichloromethane. Figure 8 As can be seen in Figure b, when the material comes into contact with n-hexane in the upper layer of water, n-hexane can be quickly absorbed into the material within seconds, and static separation of n-hexane and water can be achieved, and no red pollutants are observed in the water. Figure 8 As shown in Figure a, when the material comes into contact with dichloromethane in the water layer, dichloromethane can be quickly absorbed into the material within seconds, and static separation of water and dichloromethane can be achieved, and no red pollutants are observed in the water. In summary, it can be shown that the material has high separation efficiency and is pollution-free.
[0083] (IV) Continuous oil-water separation capability of PDMS@CMIL-101 / CS
[0084] The continuous oil-water separation ability of PDMS@CMIL-101 / CS was investigated. Fig. 9 .
[0085] Fig. 9 In the process, one end of the peristaltic pump catheter is inserted into PDMS@CMIL-101 / CS, and this end is placed in the light oil / water (heavy oil / water) mixture. Driven by the peristaltic pump, the organic phase is gradually transferred to the beaker at the other end of the catheter. After the separation, there is no residue in the aqueous phase and the organic phase.
[0086] (V) Magnetic response characteristics of PDMS@CMIL-101 / CS
[0087] The magnetic response characteristics of PDMS@CMIL-101 / CS were investigated. Due to the magnetic properties of CMIL-101, PDMS@CMIL-101 / CS floating on the water surface can be easily controlled and moved to the designated contaminated area under the influence of an external magnetic field, thereby achieving self-driven oil absorption. Based on the above driving principle and structural design.
[0088] Fig.10 The optical image of PDMS@CMIL-101 / CS aerogel in clockwise spiral motion is shown. Under the action of the magnet, PDMS@CMIL-101 / CS absorbs oil on the water surface accurately and quickly according to the spiral trajectory, which also shows that PDMS@CMIL-101 / CS does have the characteristics of magnetic stimulation response.
[0089] (VI) Photothermal conversion performance of PDMS@CMIL-101 / CS
[0090] The photothermal conversion performance of PDMS@CMIL-101 / CS was investigated.
[0091] Fig.11 The penetration behavior of high viscosity oil (peanut oil) on the PDMS@CMIL-101 / CS surface with and without simulated sunlight is shown. Without simulated sunlight, the oil droplet takes about 7 seconds to be completely absorbed ( Fig.11 In contrast, it takes only 2 seconds to completely absorb the same oil droplet under 1 simulated sunlight exposure ( Fig.11 b), which increased the permeability by nearly 3 times. In addition, peanut oil has a low-temperature response when exposed to light, indicating that peanut oil is heated in situ by collecting solar energy through PDMS@CMIL-101 / CS. This further verifies that PDMS@CMIL-101 / CS has good lipophilicity and self-heating properties, which can improve the flow of high-viscosity oils and accelerate oil absorption.
[0092] (VII) Investigation of the mechanical stability of magnetically responsive superhydrophobic PDMS@CMIL-101 / CS
[0093] The chemical stability of PDMS@CMIL-101 / CS was investigated. The surface stability and durability of PDMS@CMIL-101 / CS play a vital role in practical applications.
[0094] like Fig.12 As shown, when exposed to various harsh environments such as strong salt, strong acid, high temperature and freezing, PDMS@CMIL-101 / CS will not lose its superhydrophobicity and maintain good water resistance, and the contact angle can still be maintained above 150°, proving that they have good chemical stability.
Claims
1. A method for preparing a magnetically responsive multifunctional super-hydrophobic biomass aerogel, characterized in that: The steps include: 1) dissolving ferric chloride hexahydrate in N,N-dimethylformamide to form solution A, dissolving terephthalic acid in solution A to form solution B, hydrothermal reaction, centrifugal washing, drying, and calcining to obtain CMIL-101; 2) adding CMIL-101 to deionized water, adding chitosan CS and acetic acid, stirring vigorously to form a high-viscosity chitosan hydrogel, and freeze-drying to obtain CMIL-101 / CS aerogel; 3) The hydrophobic material and the curing agent are dissolved in an organic solvent and stirred to obtain a uniform suspension, the CMIL-101 / CS aerogel is immersed in the suspension, and then the mixed system is vacuum dried to obtain a magnetically responsive multifunctional super-hydrophobic chitosan aerogel PDMS@CMIL-101 / CS.
2. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of ferric chloride hexahydrate to terephthalic acid is 2:1; the hydrothermal reaction is carried out at 110° C. for 20 h; and the calcination is carried out at 500° C. for 2 h.
3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of chitosan CS:CMIL-101 is 5 to 10:
1.
4. The preparation method according to claim 1, characterized in that: In step 3), the hydrophobic material is selected from stearic acid, lauric acid, PFTEOS or polydimethylsiloxane; the curing agent is diphenylbutyl carbamate; and the organic solvent is n-hexane.
5. Application of the magnetically responsive multifunctional super-hydrophobic biomass aerogel PDMS@CMIL-101 / CS prepared by the preparation method according to any one of claims 1 to 4 as an adsorbent in removing organic pollutants.
6. The use according to claim 5, characterized in that: The method is as follows: take an aqueous solution containing organic pollutants, adjust the solution to neutrality, then add magnetically responsive multifunctional superhydrophobic biomass aerogel PDMS@CMIL-101 / CS, oscillate and adsorb, and then separate using a magnet.
7. The use according to claim 5, characterized in that: The organic pollutants are microplastic organic matter.
8. Application of the magnetically responsive multifunctional super-hydrophobic biomass aerogel PDMS@CMIL-101 / CS prepared by the preparation method according to any one of claims 1 to 4 as an adsorbent in oil-water separation.
9. The use according to claim 8, characterized in that: The method is as follows: add magnetically responsive superhydrophobic chitosan aerogel PDMS@CMIL-101 / CS into the oil-water mixture and let it stand for adsorption.
10. The use according to claim 9, characterized in that: The oil includes n-hexane, n-pentane, dichloromethane, ethyl acetate, N,N-dimethylformamide, chloroform, motor oil, peanut oil or olive oil.
Citation Information
Patent Citations
Preparation method of magnetic porous carbon / ferric oxide nano composite material for oil-water separation
CN103908947A
Aminated magnetic hydrothermal carbon-MOFs adsorbent as well as preparation method and application thereof
CN114984931A
Magnetic response super-hydrophobic chitosan aerogel and application thereof in MPs adsorption and oil-water separation
CN116983963A
Magnetically invasive plant hydrothermal carbon-Fe-based MIL-100 adsorbent as well as preparation method and application thereof
CN117482898A
Preparation method for magnetic super-hydrophobic starch-based aerogel useful for oil-water separation
WO2023098009A1
Cited By
Kiloton transformer dangerous waste oil treatment system and application
CN120288387A
Reversible hydrophilic / hydrophobic magnetic biomass foam material as well as preparation method and application thereof
CN120479392A
Chitosan / activated carbon / bentonite composite aerogel as well as preparation method and application thereof
CN120586841A
Force response type aerogel particle material as well as preparation method and application thereof
CN121651374A
